Clinical Outcome of Arthroscopic Treatment of Anterior Ankle Pathologies - TUNCER, Kutsi; KÖSE, Mehmet; TOPAL, Murat; ŞENOCAK, Eyüp; YILDIRIM, Ömer Selim (Ordu University, 2019)
Objective: The ankles that are the main organs cause standing over the earth can be damaged by different reasons. The ankles become painful with the problems like impingement syndrome that is soft tissue hipertrofies, osteochondral defects that is cartilage damages, traumatic or degenerative arthropaties, intraarticular tumoral tissues and some problems like that. These painful ankles can be treated with conservative methods. If it is impossible to treat painful ankles with conservative way it can be treated by minimal invasive ankle arthroscopy that is cheaper and much more satisfied, of treatment. Methods: We aim to evaluate the results and effectiveness of arthroscopic treatment of the patient who has the forefoot disorders. Also, we hope to compare the advantages, difficulties and probable complications of the arthroscopic treatment according to conservative therapy and to investigate the factors that can effect the clinical results. The 40 patients who were practiced and operated with ankle arthroscopy who was followed at least one year were compared statistically with pre-op and post-op condition. By this way the effectiveness of arthroscopy for the patients who have anterior ankle problems was determined and the main factors that effect the results were investigated. According to the result of statistical analyses preop and postop AOFAS and NPS score avarages were found clear different to each other. Results: The ankle arthroscopy that is practised by experienced surgeons with an appropriate procedure after a good clinical practise and a proper indication causes a high patient satisfaction and it causes less and temporary complications. Because of all these reasons we believe that the ankle arthroscopy can be practised by the appropriate surgeon to the appropriate patient population. Conclusion: We believe that the outcomes of ankle arthroscopy performed properly by experienced hands after determining the patient population who were accurately diagnosed by careful clinical examination and necessary imaging methods are greatly satisfactory, and the acceptability is high thanks to complications being less and usually transient.
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi; ankle arthroscopy; ankle pathologies; anterolateral impingement; osteochondral defect; ankle arthrosis; 3. Good health